Serapan Anggaran UIN Syarif Hidayatullah Jakarta: Sebelum dan Sesudah Revisi Anggaran - Nur Wachidah Yulianti (Akuntabilitas, 2019)
This research aims to see whether there are mean differences in budget absorption before and after the budget revision carried out by Syarif Hidayatullah State Islamic University Jakarta in 2017. In 2017, it is known that Syarif Hidayatullah State Islamic University Jakarta has made 8 budget revisions. At the end of 2017, the average budget absorption before revision was 86.27% and the average budget absorption after revision was 86.11%. By using paired sample t test, the test result shows a significance value (2-tailed) of paired samples test between budget absorption before revision and budget absorption after revision of 0.036 or below alpha 0.05. These result indicates that there is a mean difference between budget absorption before the budget revision and the budget absorption after the budget revision of Syarif Hidayatullah State Islamic University Jakarta in 2017.